Diseminasi Teknologi Tepat Guna Pengembangan Produk Olahan Sagu untuk Peningkatan Ekonomi UMKM di Kabupaten Manokwari - Papua Barat: Dissemination of Appropriate Technology for Sago Processed Product Development to Improve the UMKM Economic in Manokwari - West Papua - Tethool, Eduard Fransisco; Jading, Abadi; Dewi, Angela Myrra Puspita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Sago utilization in Papua has not been maximized due to the limited knowledge and abilities of local communities. This technology dissemination activity aims to increase the utilization of local Papuan resources as a substitute for wheat, by applying the equipment and processing methods that have been developed. The method used is tool dissemination and training on sago starch modification and the manufacture of various processed products in the development of business units. Prototype technology disseminated in the form of starch acidification equipment and drying equipment with UV irradiation. The trial results showed that the capacity of the acidification tool produced was 50 kg of wet sago starch (50% moisture content) with an acidification process duration of 3 days. Meanwhile, the capacity of the dryer is 25 kg of wet sago starch (50% moisture content) with a drying time of ± 20 hours. The use of disseminated tools can reduce material contact with contaminant sources resulting in better product quality.